A Content Analysis of Pictorial Material in The Chemistry Textbooks on The Topic Redox Reaction Based on Chemical Representation - Afifah, Siti Nur; Mahardiani, Lina; Utami, Budi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
Chemical representations can assist learning in understanding abstract concepts. Images can transform complex information into a form that is easier to interpret and understand. Therefore, the requirement of visual representations in chemistry textbooks is beneficial and necessary to enhance understanding of chemistry. This qualitative descriptive study analyses pictorial material related to redox reactions in chemistry textbooks based on chemical representation. This study analyzed three chemistry textbooks for 10th senior high school from different publishers that met the criteria in the purposive sampling specified. The three books contain topic redox reactions, 2013 curriculum, already have an ISBN, are used by schools, and have interesting pictures or illustrations. The instrument was developed based on the five criteria for chemical representation. Cohen Kappa coefficient was used to measure inter-rater agreement. The results show this study has an almost perfect agreement (0,891). The pictorial material in the three textbooks has macroscopic, submicroscopic, multiple, and mixed types of visual representation. The study analyzed the pictorial material or visual content in three chemistry textbooks (books A, B, and C). The results showed that the type of visual representation with the highest percentage was macroscopic, which was 58.33% in book A, 50% in book B, and 57.14% in book C. The highest proportion of ambiguous interpretation of surface features was found in topic redox reaction compared to other typologies, which was 50% in book A, 50% in book B, and 57.14% in book C. Most of the images in the textbooks were completely related and linked to the text and had image captions. The textbooks had a high level of relatedness to the text, with completely related-linked percentages of 66.67% in book A, 70% in book B, and 57.14% in book C. The study found that the pictorial material presented in the three books met the standard criteria of chemical representation. The study's findings can be used as a reference for teachers to determine student learning resources for chemistry textbooks with appropriate chemical representations, which can help improve students' understanding of the subject.